Altered fear processing in adolescents with a history of severe childhood maltreatment: an fMRI study. Issue 7 (12th February 2018) - Hart, H.; Lim, L.; Mehta, M. A.; Simmons, A.; Mirza, K. A. H.; Rubia, K.
Abstract: Background: Children with a history of maltreatment suffer from altered emotion processing but the neural basis of this phenomenon is unknown. This pioneering functional magnetic resonance imaging (fMRI) study investigated the effects of severe childhood maltreatment on emotion processing while controlling for psychiatric conditions, medication and substance abuse. Method: Twenty medication-naive, substance abuse-free adolescents with a history of childhood abuse, 20 psychiatric control adolescents matched on psychiatric diagnoses but with no maltreatment and 27 healthy controls underwent a fMRI emotion discrimination task comprising fearful, angry, sad happy and neutral dynamic facial expressions. Results: Maltreated participants responded faster to fearful expressions and demonstrated hyper-activation compared to healthy controls of classical fear-processing regions of ventromedial prefrontal cortex (vmPFC) and anterior cingulate cortex, which survived at a more lenient threshold relative to psychiatric controls. Functional connectivity analysis, furthermore, demonstrated reduced connectivity between left vmPFC and insula for fear in maltreated participants compared to both healthy and psychiatric controls. Conclusions: The findings show that people who have experienced childhood maltreatment have enhanced fear perception, both at the behavioural and neurofunctional levels, associated with enhanced fear-related ventromedial fronto-cingulate activation and altered functional connectivity with associated limbic regions. Furthermore, the connectivity adaptations were specific to the maltreatment rather than to the developing psychiatric conditions, whilst the functional changes were only evident at trend level when compared to psychiatric controls, suggesting a continuum. The neurofunctional hypersensitivity of fear-processing networks may be due to childhood over-exposure to fear in people who have been abused.